Boys and Girls in Developing Scientific Literacy Through PBL Supported by ClimateClass - Wisnu Juli Wiono; Ismi Rakhmawati; Yudianto (Jurnal BIOEDUIN : Program Studi Pendidikan Biologi, 2025)
This study examines the effectiveness of the Problem Based Learning (PBL) model supported by the Android application ClimateClass in developing students' science literacy skills. Science literacy is crucial in the 21st century as it equips students with the necessary skills to make informed decisions in a technology-influenced society. Despite Indonesia's participation in international programs like PISA, the level of science literacy in the country remains low, indicating the need for innovative educational strategies. This quasi-experimental research used a pretest-posttest non-equivalent control group design conducted at SMA Negeri 1 Padang Cermin Pesawaran with a sample of 36 students from Class X.2. The intervention involved the implementation of the PBL model with the ClimateClass application to facilitate a more interactive and problem-solving-focused learning environment. Data were collected using a science literacy test and a questionnaire and analyzed using ANCOVA to determine the significance of the intervention. The results showed that the use of the PBL model supported by the ClimateClass application significantly developed students' science literacy, particularly in identifying scientific issues, explaining scientific phenomena, and using scientific evidence. Moreover, the study found no significant differences in science literacy achievement between male and female students, indicating that gender does not affect learning outcomes in this context. These findings highlight the potential of integrating digital media into educational models to create an equitable and effective learning environment in the digital era.